Implementasi Algoritma Kriptografi AES (Advanced Encryption Standard) 128 Bit Untuk Pengamanan Dokumen Shipping - Nuari, Rivian; Ratama, Niki (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2020)
In the shipping document data storage is stored just like that without any special safeguards. to overcome the problem above, we need a way to secure the data with a fast time, so it is not misused. The researcher's goal is to use a description-encryption technique with the 128-bit AES algorithm into a system because it has a level of resistance to all types of attacks to avoid loss and theft and reduce the risk of damage to data / files. The process of encrypting and describing document files using the AES 128 bit (Advanced.Encryption Standard) algorithm. In data / files, the encryption process (1 block) of plaintext is first converted to ASCII code in hexadecimal numbers and formed as a 4x4 byte matrix called state. The encryption process in AES 128 is a transformation of the state repeatedly in 10 rounds. Data processed in each round is binary data. Each AES round requires one key generation key result and uses 4 basic transformations namely subbytes, shiftrows, mixcolumns, and addroundkey. Whereas the decryption process has transformations in the order of invshiftrows, invsubbytes, addroundkey, and invmixcolumns. In document files that have been confirmed to have a number of characters more than 16 characters the encryption and decryption process will be performed every 128 bits or 16 characters. So that the AES encryption and decryption process is done in parallel. Whereas for text files with less than 16 characters, padding will be performed. Padding is the use of null ASCII characters to fill in the number of characters that are lacking in order to be processed and will not affect the results of encryption or decryption.